2002
DOI: 10.1016/s0014-5793(02)02614-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of casein kinase Iα interacting protein partners

Abstract: Casein kinase IK K (CKIK K) belongs to a family of serine/threonine protein kinases involved in membrane trafficking, RNA processing, mitotic spindle formation and cell cycle progression. In this report, we identified several CKIK K interacting proteins including RCC1, high mobility group proteins 1 and 2 (HMG1, HMG2), Erf, centaurin-K K 1 , synaptotagmin IX and CPI-17 that were isolated from brain as CKIK K co-purifying proteins. Actin, importin-K K 1 , importin-L L, PP2Ac, centaurin-K K 1 , and HMG1 were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Several studies have confirmed that this protein family is involved in the cell cytoskeleton [9][10][11] and regulates actin cytoskeleton organization in vivo as a GTPaseactivating protein (GAP) of ARF6 [12], a member of the ARF family of GTPases [13]. In addition, identifications of associations of centaurin-a1 with casein kinase Ia (CKIa) [14,15], Ran binding protein in microtubule-organizing center (RanBPM) [16], kinesin motor protein (KIF13B) [17,18] and protein kinase C (PKC) [19] further indicates the significant potential of centaurin-a1 in cellular cytoskeletal remodeling, vesicle trafficking and thus cellular innate immunity.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have confirmed that this protein family is involved in the cell cytoskeleton [9][10][11] and regulates actin cytoskeleton organization in vivo as a GTPaseactivating protein (GAP) of ARF6 [12], a member of the ARF family of GTPases [13]. In addition, identifications of associations of centaurin-a1 with casein kinase Ia (CKIa) [14,15], Ran binding protein in microtubule-organizing center (RanBPM) [16], kinesin motor protein (KIF13B) [17,18] and protein kinase C (PKC) [19] further indicates the significant potential of centaurin-a1 in cellular cytoskeletal remodeling, vesicle trafficking and thus cellular innate immunity.…”
Section: Introductionmentioning
confidence: 94%
“…In light of previous biochemical evidence for interactions between CK1 and the protein phosphatases PP1/PP2 A and between PP1/PP2 A and NMDA receptors (Agostinis et al, 1987;Marin et al, 1994;Westphal et al, 1999;Chan and Sucher, 2001;Dubois et al, 2002), we hypothesized that the protein phosphatases PP1 and/or PP2 A could be intermediary elements between CK1 and NMDA receptors. To examine whether inhibition of protein phosphatases might mediate the effect of CK1-7 on NMDA receptor activity, we applied the PP1/PP2 A inhibitor okadaic acid in either the perfusion solution or the intracellular solution and examined the effect of CK1-7 on NMDA-EPSCs.…”
Section: Inhibition Of Pp1/pp2mentioning
confidence: 99%
“…p42 IP4 can shuttle between cytosol, nucleus and plasma membrane, depending on the cell stimulation situation . Several interaction partners of p42 IP4 have been identified, such as casein kinase I (Dubois et al 2001(Dubois et al , 2002, nucleolin , protein kinase C , several ARFs (Thacker et al 2004;Venkateswarlu et al 2004) GAKIN (Venkateswarlu et al 2005;Horiguchi et al 2006), the peptidase nardilysin (Stricker et al 2006) or F-actin (Thacker et al 2004). It has been shown that p42 IP4 is a component of the neuronal phosphatidyl inositol 3-kinase cascade and is involved in dendritic differentiation/synaptic plasticity and/or transport of PtdIns(3,4,5)P 3 -containing vesicles along axons to regulate neuronal cell polarity (Horiguchi et al 2006;Moore et al 2007).…”
mentioning
confidence: 99%